To come to the land : immigration and settlement in sixteenth-century Eretz-Israel - David, Avraham (Judaic studies series., 1999)
To Come to the Land makes available in English a vast body of research, previously available only in Hebrew, on the early history of the land now known as Israel. Abraham David here focuses on the Spanish and Portuguese Jews who fled the Iberian Peninsula during the 16th century, tracing the beginnings of Sephardic influence in the land of Israel. After the Ottoman Turks conquered Syria, Palestine, and Egypt in 1516, the Ottoman regime, unlike their Mamluk predecessors, encouraged economic development and settlement throughout the regime.